In Silico Study of Histo-aspartic Protease (HAP) Inhibitor from Indonesian Medicinal Plants: Anti-malarial Discovery - Dinar Mutia Rani; Muhammad Habiburrohman; Yoshinta Debby; Bawon Triatmoko; Ari Satia Nugraha (Nusantara Science and Technology Proceedings)
Malaria is an infectious disease caused by Plasmodium sp with the highest clinical incidence of 12.07% in Indonesia. New anti-malaria compounds are needed to replace antimalarial drugs that are already resistant nowadays. One of the efforts to find a new anti-malaria drug is through research on traditional medicinal plants used by Indonesian tribes from the ethnopharmacology database. In silico studies provide saving solutions in the process of computer-aided drug design. Histo-aspartic protease (HAP) is essential for the growth of Plasmodium falciparum and has been validated as an antimalarial drug target. Therefore, molecular docking was used to provide new insights into the development of drugs by targeting HAP protease. There are 238 compounds from 43 medicinal plants used as targeting ligand in this study prepared by Autodock Vina for an automated docking tool. The comprehensive docking protocol was valid showed by the RMSD value of 1,275 Å. The result obtained that AM50 (borrasosides A) from Borassus flabellifer was found to have the least affinity score of -10.1 kcal/mol higher compared to the native ligand. In conclusion, we are assuming that the mechanism of borrasosides A compound might get involved with HAP. Further protocols are required to prove the HAP inhibition towards Plasmodium falciparum.